Implementasi Program Pos Upaya Kesehatan Kerja (UKK) di Wilayah Kerja Puskesmas Tahtul Yaman Kota Jambi - Faridah, Faridah; Hasmar, Wanti (Universitas Baiturrahim, 2025)
According to information from the program holder, the Occupational Safety Post at the Tahtul Yaman Community Health Center in Jambi was established in 2021 under the name Kapal Sanggat UKK Post. In 2023, the